SHE’S - Rosalia Novia Ariswari (Saraswati)
She’s is a dance work inspired by personal experience that seeing from a mother figure. Gentleness, have high fighting spirit, and have a responsibility beyond the weakness of woman seen from the figure of mother. This work is a dance piece performed by two young dancers with different roles, the portrayal of a mother by a dancer, and describe a child by another dancer.  Excitatory  idesional  is  the  beginning  of  making  this  work.  Dramatic dance type used in this work with the presentatin of symbolic representational mode. Issue that are closest to life stylist of choice in making this work. Interest and admiration inthe eyes of a mother figure to inspire artist to create and dedicate this work to formidable mother in their daily lives.   Keywords: mother, woman, fighting spirit